MENANTI GELIAT SASTRA TERJEMAHAN SASTRA BALI MODERN - I Wayan Juliana (Subasita: Jurnal Sastra Agama dan Pendidikan Bahasa Bali, 2020)
The life of modern Balinese literature has experienced a prestigious increase. It can be proved by a lot of great works from old and new authors. The publishments also increase enormously. It is a kind of pride for Balinese literatures lovers Society because the literatures keep alive on the term of spoken and written form. On the other hand, the Balinese translation has not obtained significant attention yet. The author and everyone who concerns into it write their experience the most rather than translate literatures in Bahasa or foreign language into Balinese language. Keywords: literatures, translated literatures, Modern Balinese literature